ANALISIS YURIDIS TERHADAP PUBLIKASI IDENTITAS ANAK BERHADAPAN DENGAN HUKUM PADA SITUS DIREKTORI PUTUSAN MAHKAMAH AGUNG - Perdana, Fharysha Irwan; Erdianto, Erdianto; Erdiansyah, Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Children who are in conflict with the law, even though they are suspectedof having committed a criminal act, still have the right to protection by the state,especially regarding their identity. The Supreme Court Decision Directory as asite that contains information about Supreme Court decisions, including asummary of decisions, legal considerations, and links to complete decisionsshould pay attention to the importance of not publishing the identity of children inconflict with the law when uploading copies of decisions. Publication of theidentity of children in conflict with the law can have a very bad impact onchildren, such as stigmatization and discrimination which can affect their future.The type of research used in this research is normative juridical legalresearch or can also be called doctrinal legal research. Normative juridical legalresearch is library legal research. The research uses qualitative analysis whichproduces descriptive data.From the results of this research, there are several main things that can beconcluded. First, the Law on the Juvenile Justice System stipulates that theidentity of children in conflict with the law must be kept confidential, both in printand electronic media, but in reality there are still many decisions that do notobscure the child's identity before being uploaded to the Supreme Court DecisionDirectory website. such as decision Number 18/Pid.Sus-Anak/2021/Pn Srg whichexplicitly shows the identity of the child as the perpetrator, the name of theparents, and the place of residence where the decision can be accessed by thepublic. Second, the Supreme Court Directory's information officer's mistake inpublishing a copy of the child's decision may result in administrative sanctions,but in enforcing these sanctions it does not provide a deterrent effect so thatcriminal regulations as an ultimum remedium or as a final resort in lawenforcement are expected to provide a deterrent effect for Directory officers. TheSupreme Court is responsible for the case.Keywords: Publications, Child Identity, Supreme Court Directory.